Cytotoxic activity of crude extracts and fractions of African peach (nauclea latifolia smith) stem bark on two cancer cell lines - Oluwakemi Charles-Okhe; Michael A. Odeniyi; Titilayo O. Fakeye; Omonike O. Ogbole; Toluwanimi E. Akinleye; Adekunle J. Adeniji (Elsevier, 2022)
Background: The purpose of this research work is to investigate and establish the anticancer (cytotoxic) properties of African peach (Nauclea latifolia) stem bark extract and fractions on breast cancer cell lines (MCF-7), skeletal muscle cancer (RD) cell lines and to determine the selectivity index (SI) on normal African green monkey kidney cell lines (Vero). Materials and Methods: Crude extract and fractions obtained from acid-base fractionation and vacuum liquid chromatography (VLC) using graded concentrations of hexane, methanol, ethyl-acetate to obtain sample A to G. These samples were tested against standard cancer cell lines (MCF-7 -breast cancer; RD cells- skeletal muscle cancer) and normal Vero cell lines to determine the cytotoxicity based on the IC50 generated. The anticancer activity was evaluated using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide colorimetric assay against two cancer cell lines at six different concentrations from 0.01 to 1000 µg/mL. The data generated were analyzed with Graph Pad prism 5 to obtain the IC50. Results: Sample C- neutral fraction gave IC50 values of 3.23 µg/mL and 13.15 µg/mL for MCF-7 and RD respectively. Sample D- Hexane/ethyl acetate fraction 50:50 gave IC50 values of 16.70 µg/mL and 8.97 µg/mL for MCF-7 and RD respectively. Sample B- basic fraction had IC50 of 20.51 µg/mL and 16.96 µg/mL for MCF-7 and RD respectively. Sample G- Methanol fraction had IC50 of 28.56 µg/mL and 22.52 µg/mL for MCF-7 and RD respectively. These four samples exhibited significant anticancer activities on the MCF-7 and RD cancer cell lines. These values are comparable to that of vincristine used as standard anticancer drug with IC50 of 0. 82 µg/mL and 6.31 µg/mL for MCF-7 and RD cell lines respectively. The selectivity index (SI) of three samples was carried out using Vero cell line and sample C - neutral fraction had the best selectivity against the cancer cell lines under investigation. Conclusions: Nauclea latifolia fractions have profound cytotoxic activities when tested in vitro on standard cancer cell lines and could be considered as a potential chemotherapeutic agent.